Application of Geo-informatics technology for plant genetic conservation project, Rajamangala University of Technology Lanna - Joobanjong, Wanchana; Mulom, Rung; Thungrabeab, Malee; Suesatsakulchai, Apichai (RMUTSB ACADEMIC JOURNAL, 2025)
Carbon sequestration plays a crucial role in mitigating the greenhouse effect and reducing the severity of climate change. The application of geographic information technology is essential for systematic data collection and visualization, supporting research and strategic planning for expanding green spaces to enhance carbon sequestration. This study focuses on developing a web-based geographic information system (GIS) of tree data management and evaluation the carbon sequestration capacity of trees within the study areas of the plant genetic conservation project at Rajamangala University of Technology Lanna (RMUTL). The research was conducted in three designated study areas: RMUTL Tak, RMUTL Lampang, and the Agricultural Technology Research Institute. The study was structured into three phases. The first phase involved collecting tree data and geolocation coordinates to be integrated into the GIS platform for spatial visualization and carbon sequestration assessment. The second phase employed unmanned aerial vehicles (UAVs) to capture aerial imagery, generate three-dimensional (3D) geographic models, and create cross-sectional representations of the study areas. The final phase focused on developing a GIS web platform to display tree data, geospatial coordinates, 3D models, and cross-sectional imagery. The study successfully collected data on 738 trees across 11 plots, covering a total area of 491,462 square meters, with an estimated carbon sequestration capacity of only 167,559.28 kilograms. The UAV-based image processing produced two 3D geographic models and eight cross-sectional images, showing all integrated into the GIS platform. The developed system provides tree-related data and spatial information. This system was serving as a valuable decision-support tool for environmental planning and conservation initiatives. The findings of this study contribute to evidence-based strategies for enhancing carbon sequestration at RMUTL, which may support broader national efforts to mitigate climate change.